Lavoro, azienda e tecnologia. Riflessioni su un'esperienza di antropologia applicata - Balella, Chiara (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
This article presents a field research as an example of anthropological study applied to the working dynamics within an Italian ICT company. This experience is narrated through three levels of reflection linked by the theme of “differences”: the disciplinary differences relating to labor studies in Italy, where anthropology is much less developed and considered than close disciplines; the differences in the analysis of working dynamics in the company, where it’s usually made a break between working climate -investigated by psychology through quantitative tools- and working culture -studied by anthropology through qualitative methods-; the differences in the perception of technological work in the company, where technology is often separated from human labor. A positive outlook towards the future and the awareness of an anthropology which is both action, commitment, participation and experimentation try to create a new balance between these differences.